2000
DOI: 10.1002/1521-4095(200008)12:16<1173::aid-adma1173>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Gel Nanoparticle Networks

Abstract: A new class of nanostructured polymer gel is reported here, in which polymer nanoparticles, rather than monomers, are covalently crosslinked. Since their building blocks are nanoparticles, the thus formed networks have novel and unique properties compared with conventional gels, for example, a very high surface area for better bioadhesion, and a uniform and tunable mesh size for controlled drug delivery. Several networks are presented, including one with a fast shrinkage rate, a colored network, and a co‐nanop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
78
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(79 citation statements)
references
References 13 publications
0
78
1
Order By: Relevance
“…Most polymer materials that exhibit structural color are based on the incorporation of periodically packed colloidal particles into the polymer matrix, or the formation of a porous polymer matrix by etching away the precursor colloidal particles [37][38][39][40][41][42][43][44][45]. These photonic crystalline materials are therefore isotropic in structure, they have poor color quality and weak mechanical response, and their color tuning ability covers narrow wavelength band (< 70 nm).…”
Section: Mechano-responsive Color Tunabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Most polymer materials that exhibit structural color are based on the incorporation of periodically packed colloidal particles into the polymer matrix, or the formation of a porous polymer matrix by etching away the precursor colloidal particles [37][38][39][40][41][42][43][44][45]. These photonic crystalline materials are therefore isotropic in structure, they have poor color quality and weak mechanical response, and their color tuning ability covers narrow wavelength band (< 70 nm).…”
Section: Mechano-responsive Color Tunabilitymentioning
confidence: 99%
“…The well ordered anisotropic structures of the biological tissues enable highly elaborate functions of living organisms [11][12][13][14][15]. For example, actins and myosin show a liquid crystalline anisotropic structure in a muscle sarcomere, which contributes the smooth motion of muscle fibers and muscle contraction in a specific direction [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated that this kind of composite hydrogel can be used to control the delivery of bovine serum albumin (BSA) in response to changes in temperature. Hu et al [41] have reported the preparation of hydroxypropyl cellulose (HPC) polymer gel nanoparticles networks where HPC gel nanoparticles were cross-linked via covalent bonding, resulting in a faster responsive rate in shrinking. Nowadays, preparation of new macroscopic composite gels from conventional polymers by simple and green chemistry presents a big challenge for their high potential applications.…”
Section: Full Papermentioning
confidence: 99%
“…It has previously been reported [40] that the shrinkage rate of a gel is strongly dependent on the size of the gel. Tanaka and Fillmore [40,41] significantly reduce the response time, so many kinds of PNIPAAm microgels or nanogels have been prepared [32]. However, microgels are too small for some applications and also are not easy to handle.…”
Section: Shrinkage Kineticsmentioning
confidence: 99%